All different but all equal?: the role of age on the relationship between hr practices and turnover intention and employee well - Silva, Sofia Alexandra Faustino da (2020)
In recent decades there has been a global aging phenomenon, resulting in a more age diverse workforce. This phenomenon represents a challenge for organizations, which have the need to attract and retain the best talents through Human Resource Management (HRM). Prior research has shown inconsistencies on the study of the impact of age in the relation between human resources (HR) practices and work-related outcomes. Drawing on Social Exchange, Signaling and Conservation of Resources theories, this research aims to examine the role of chronological age and life stage in the relationship between HR practices and individual (i.e. well-being) and organizational outcomes (i.e. turnover intention). A sample of 365 employees participated in this time-lagged study, by answering to two questionnaires. Three bundles of HR practices were studied. Development Practices (HRDP), Maintenance Practices (HRMP) and Flexible Practices (FWP) showed a negative impact on turnover intention. However, only HRDP positively influenced well-being. Further, nor age nor life stage moderated the relation between HR practices and the studied outcomes. Findings suggest that to retain employees and promote their well-being, organizations should provide HRDP, HRMP and FWP to all employees, regardless of age or life stage. This research contributes to the HRM literature, by showing that age does not moderate the impact of these practices on individual and organizational outcomes, and that professional development is an important part of well-being.